Sleep Quality and Associated Factors Among Diabetes Mellitus Patients in a Follow-Up Clinic at the University of Gondar Comprehensive Specialized Hospital in Gondar, Northwest Ethiopia: A Cross-Sectional Study - Birhanu, Tesfamichael Tadesse (Diabetes Metab Syndr Obes, 2020)
INTRODUCTION: Diabetic mellitus has a negative impact on the quality of sleep. It is one of the leading public health conditions which can result in poor sleep quality. Poor sleep quality is an unreported and unrecognized problem which can affect the prognosis of diabetes patients. OBJECTIVE: The aim of this study is to assess the prevalence of poor sleep quality and its associated factors among patients with diabetes mellitus attending follow-up clinics at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2019. METHODS: An institution-based cross-sectional study was conducted among 430 diabetes mellitus patients at the University of Gondar Comprehensive Specialized Hospital from February 1, 2020 to March 28, 2020. A systematic random sampling method was used to reach the study subjects. An interviewer-administered questionnaire was used for data collection. Pittsburgh sleep quality index was used for assessing sleep quality. To explain study variables, frequency tables and percentages were used. A binary logistic regression was conducted to see the relation between dependent and independent variables. RESULTS: A total of 430 diabetes mellitus patients participated in the study with a response rate of 100%. The overall prevalence of poor sleep quality was 47.2%. Drinking alcohol (AOR = 2.45, 95% CI: 1.28–4.69), smokers (AOR = 6.26, 95% CI: 2.04–19.21), comorbidity (AOR = 1.80, 95% CI: 1.10–2.96), BMI ≥ 30 (AOR = 4.87, 95% CI: 1.07–22.09), having type 2 diabetes mellitus (AOR = 2.16, 95% CI: 1.04–4.50), poor glycemic control (AOR = 2.61, 95% CI: 1.81–4.81) and having depression (AOR = 9.95, 95% CI: 4.85–20.38) were associated with poor sleep quality. CONCLUSION: In this study, nearly half of the patients had poor sleep quality. Drinking alcohol, smoking, comorbidities, higher BMI, type 2 diabetes mellitus, poor glycemic control and having depression were factors in poor sleep quality. Creating awareness of the need for weight reduction, minimizing alcohol intake, cessation of smoking, and improving sleep hygiene for DM patients would be effective management for improving poor sleep quality.